Postmodernity and Philosophy - Pałubicka, Anna (Sensus Historiae, 2023)
We all experience and possess an imagination of postmodernity, yet we describe it in highly individualized ways. What is lacking is a universally accepted vision of postmodernity. Even postmodernism, which focused mainly on critiquing modernist philosophy, did not create such a vision. This article interprets the views of the French philosopher Q. Meillassoux, a representative of the younger generation that follows postmodernism. The author sees in Meillassoux's ideas an attempt to provide answers that resonate with many interpretations within the cultural context of postmodernity. It turns out that philosophy can still be a relevant field in culture, even in postmodernity, provided that it engages in a reflection on classical philosophical questions in relation to postmodernity. This recognition acknowledges that philosophy co-creates the cultural context and is influenced by all fields of culture, especially in the current postmodern era.